IMPLEMENTASI PENDEKATAN TEACHING AT THE RIGHT LEVEL (TaRL) TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS PADA MATERI PENYAJIAN DATA SISWA SMP - Ratu Maharani; Yadi Ardiawan; Utin Desy Susiaty (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to compare the effectiveness of the Teaching at the Right Level (TaRL) approach and conventional learning on the mathematical conceptual understanding ability of seventh-grade students at SMP Negeri 13 Pontianak in the topic of data presentation. This research employed a Quasi-Experimental Design using the Nonequivalent Control Group Design. The sample was selected through purposive sampling, consisting of Class VIIA as the experimental group (32 students), which received the Teaching at the Right Level (TaRL) approach, and Class VIIC as the control group (32 students), which received conventional learning. The research instrument was a test of mathematical conceptual understanding on data presentation material. Data were analyzed using the independent samples t-test. The results showed that both learning approaches improved students’ conceptual understanding abilities. The experimental group’s mean score increased from 31.01 to 80.08, with an average of 49.07, while the control group’s mean score increased from 30.08 to 69.73, with an average of 39.65. The independent samples t-test revealed that t_calculated = 8.1057 was greater than t_table = 1.9990 (α = 0.05), indicating that the mathematical conceptual understanding ability of students taught using the Teaching at the Right Level (TaRL) approach was significantly better than that of students taught through conventional learning. The TaRL approach enables students to learn according to their individual ability levels, thereby facilitating a better understanding of mathematical concepts.